2012
DOI: 10.1161/circulationaha.111.084806
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Clinical and Echocardiographic Follow-Up of the Freestyle Stentless Aortic Bioprosthesis

Abstract: Background-Stentless aortic bioprostheses were designed to provide enhanced hemodynamic performance and potentially greater longevity. The present report describes the outcomes of patients with the Freestyle stentless bioprosthesis followed for Յ18 years. Methods and Results-Between 1993 and 2011, 430 patients underwent primary aortic valve replacement with a Freestyle bioprosthesis in the subcoronary position. Mean age was 68.2Ϯ8.2 years. All of the clinical and echocardiographic data were collected prospecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 39 publications
(31 reference statements)
3
37
1
Order By: Relevance
“…19 A study of 430 patients treated with a stentless bioprosthesis reported freedom from reoperation in 91.0% and 75.0% at 10 and 15 years, and freedom from reoperation for SVD in 95.9% and 82.3%, respectively. 17 Notably, outcomes vary with different surgical bioprostheses as demonstrated in recent post-market surveillance of 43 782 valves in England and Wales. 20 …”
Section: Long-term Outcomes Of Bioprosthetic Valves In the Aortic Posmentioning
confidence: 99%
“…19 A study of 430 patients treated with a stentless bioprosthesis reported freedom from reoperation in 91.0% and 75.0% at 10 and 15 years, and freedom from reoperation for SVD in 95.9% and 82.3%, respectively. 17 Notably, outcomes vary with different surgical bioprostheses as demonstrated in recent post-market surveillance of 43 782 valves in England and Wales. 20 …”
Section: Long-term Outcomes Of Bioprosthetic Valves In the Aortic Posmentioning
confidence: 99%
“…The immediate need for re-operation for haemostasis following FSB implantation is inconsistently reported in the literature [7,11] but has been reported as up to 9.5% [13]. This is not unexpected given the extent of additional aortic replacement surgery that may be required and associated coagulopathy that can develop.…”
Section: Discussionmentioning
confidence: 98%
“…Ltd.) is a porcine aortic bioprosthesis particularly suitable for use where concurrent aortic root replacement surgery is necessitated by thoracic aortic disease. Long-term clinical and echocardiographic data are available up to 15 years post-operatively for the Freestyle, with promising results evident thus far [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transvalvular regurgitation occurs as a result of restricted leaflet motion or leaflet destruction and improper sizing or overdilatation of the valve during the implantation. If the prosthesis has been implanted too low in the aortic position a special form of regurgitation termed supraskirtal could develop (28)(29)(30)(31).…”
mentioning
confidence: 99%